2011
DOI: 10.1007/s10456-011-9241-1
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes released by K562 chronic myeloid leukemia cells promote angiogenesis in a src-dependent fashion

Abstract: Exosomes, microvesicles of endocytic origin released by normal and tumor cells, play an important role in cell-to-cell communication. Angiogenesis has been shown to regulate progression of chronic myeloid leukemia (CML). The mechanism through which this happens has not been elucidated. We isolated and characterized exosomes from K562 CML cells and evaluated their effects on human umbilical endothelial cells (HUVECs). Fluorescent-labeled exosomes were internalized by HUVECs during tubular differentiation on Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
208
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(221 citation statements)
references
References 39 publications
11
208
1
1
Order By: Relevance
“…Furthermore, we showed that MM-MV-treated endothelial cells had enhanced levels of VEGF and IL-6, the key growth factors involved in myeloma [41] . These results support the role of MM-MVs in angiogenesis, consistent with findings in other cancers [12,14,21] . Of note, the origin of MMendothelial cells is actually unknown [42,43] .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, we showed that MM-MV-treated endothelial cells had enhanced levels of VEGF and IL-6, the key growth factors involved in myeloma [41] . These results support the role of MM-MVs in angiogenesis, consistent with findings in other cancers [12,14,21] . Of note, the origin of MMendothelial cells is actually unknown [42,43] .…”
Section: Discussionsupporting
confidence: 91%
“…Although these classical events have been commonly thought of as the predominant modes of cell-to-cell communication, a novel type of vesicle secretion has recently received a great deal of attention [8,9,15,33] . Though the secretion of exosomes by myeloma [21,34] , there have been no previous studies about MM-MVs. The current study identified MM-MVs as a potential mediator of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the KEGG pathways to analyze targets of dysregulated miRNAs across the progression of CML, we have found that many dysregulated potential target molecules were involved in several biological pathways including metabolic and cancer pathways, the MAPK signaling pathway, endocytosis, cytokine-cytokine receptor interaction and focal adhesion. Recent studies have confirmed that pathogenesis and progression of CML were closely related to the MAPK signaling pathway [27,28], endocytosis [29,30] and focal adhesion [31,32].…”
Section: Oncotarget S474 Wwwimpactjournalscom/oncotargetmentioning
confidence: 90%